Modifikasi Senam Anak Berkebutuhan Khusus (ABK) untuk Siswa/i Tunagrahita pada SLB C-YPSLB Surakarta - Adnan Faris Naufal; Rizki Setiawan; Marlita Prasetyani; Jihadilia Islami Putri; Adindha Puteri Ayu Zahwani; Muhammad Nizar Siddiq; Arif Pristianto (Universitas Islam Indonesia, 2024)
Children who are different from other kids their age or from kids in general are known as children with special needs, or ABK. The process of growth and development, which entails deviations or abnormalities on all fronts—physically, cognitively, intellectually, and socially—is one way in which these disparities appear. The findings of an investigation at SLB C-YPSLB Surakarta revealed issues with intellectual impairment and mobility disorders. When it comes to the quality of physical activity for children with mental retardation who require specialized instruction and supervision, motor development is a crucial factor. The fulfillment of physical needs is also impaired, namely sensorimotor skills, body balance, the ability to recognize the environment, body coordination and mobility, and body flexibility. Gymnastics for Children with Special Needs (ABK) was chosen as a solution to improve their motor skills. The chosen method is doing gymnastic movements together and guided by physiotherapy. Gymnastics has important benefits for health, child development now and in the future. Other benefits include strengthening children's muscles, bones and heart, as well as improving children's coordination, balance, posture and flexibility to achieve a better quality of life.